2021
DOI: 10.3390/economies9030126
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender and Educational Attainment Differences on International Migrants’ Occupational Status in OECD Countries

Abstract: The purpose of the study is to show two essential elements of the occupational status of international migrants in OECD countries. The study extends the current research by focusing on how the educational attainment of international migrants and the gender dimension affect migrants’ occupational status. To achieve the aim of the study, a quantitative research approach was followed. Ordinary least square regression analysis was used to emphasize the relationship between educational attainment and gender differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…As emphasized earlier, human capital plays an important role in immigrant entrepreneurship because human capital also differs by gender (Sanders & Nee, 1996). It has been found that female immigrants do not have sufficient human capital components compared to male immigrants (Al-Dalahmeh, Sarihasan & Dajnoki, 2021;Sarihasan, 2017).…”
Section: Gender Differences In the Role Of Human Capital In Immigrant...mentioning
confidence: 97%
“…As emphasized earlier, human capital plays an important role in immigrant entrepreneurship because human capital also differs by gender (Sanders & Nee, 1996). It has been found that female immigrants do not have sufficient human capital components compared to male immigrants (Al-Dalahmeh, Sarihasan & Dajnoki, 2021;Sarihasan, 2017).…”
Section: Gender Differences In the Role Of Human Capital In Immigrant...mentioning
confidence: 97%